Development of a Novel Double-Ring Deployable Mesh Antenna - Yan Xu; Fuling Guan; Xian Xu; Hongjian Wang; Yao Zheng (International Journal of Antennas and Propagation)
This paper addresses a type of deployable mesh antenna consisting of the double-ring deployable truss edge frame and the cable net reflector. The structural design concept of the deployable antennas is presented. The deployable truss is designed and the geometric relationship of each strut length is formulated. Two types of radial truss elements are described and compared. The joint pattern and the active cables of the final design concept are determined. The pattern of the cable net is the three-orientation grid. Two connection schemes between the reflector and the deployable edge frame are investigated. The design parameters and the shape adjustment mechanism of this cable net are determined. The measurement test technologies of the antennas on the ground including test facilities, deployment test, and measurement and adjustment test are proposed. The antenna patterns are analyzed based on the real surfaces of the reflector obtained by the reflective surface accuracy measurement. The tests and analytic results indicated that the accuracy of the reflective surface is high and is suitable for low-frequency communication.